TINJAUAN DESKRIPTIF CAGAR BUDAYA GUA NAPALICIN KABUPATEN MUSI RAWAS SUMATERA SELATAN - Nur Maimunah; Maskun Maskun; Syaiful M (FKIP UNIVERSITAS LAMPUNG, 2013)
Cultural Heritage Cave Napalicin in Musi Rawas Regency Of South Sumatera. There are efforts Musi Rawas District Governments in the preservation of cultural heritage. Purpose of this research is to find out what are the Musi Rawas Regency Government efforts in the preservation of Cultural Heritage Cave Napalicin. This research used descriptive method with data collection trough observation, interviews, documentation and literature as well as analyzing the data with qualitative data analysis techniques. The results of this study suggest that efforts Musi Rawas Regency Government in the preservation of Cultural Heritage Cave Napalicin by doing some activities there are, publication, protection and restoration. Cagar Budaya Gua Napalicinterletak di Kabupaten Musi Rawas Sumatera Selatan. Terdapat upaya Pemerintah Daerah Kabupaten Musi Rawas dalam pelestarian cagar budaya. Tujuan penelitian ini untuk mengetahui apa sajakah upaya Pemerintah Daerah Kabupaten Musi Rawas dalam pelestarian Cagar Budaya Gua Napalicin.Penelitian ini menggunakan metode deskripsif dengan teknik pengumpulan data melalui teknik observasi, wawancara, dokumentasi, kepustakaan sertateknik analisis data kualitatif. Hasil dari penelitian ini menunjukkan bahwa upaya Pemerintah Daerah dalam pelestarian Cagar Budaya Gua Napalicin dengan melakukan beberapa kegiatan yaitu pemanfaatan, pempublikasian, perlindungan dan pemugaran. Kata kunci: pelestarian cagar budaya, pemerintah, upaya